2003
DOI: 10.1176/appi.ajp.160.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Attitudes and 5-HT2 Receptors During Depression and Self-Harm

Abstract: Low levels of 5-HT agonism in the brain cortex may explain the severely pessimistic, dysfunctional attitudes associated with major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
190
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(206 citation statements)
references
References 70 publications
15
190
1
Order By: Relevance
“…In this work, we found a significant degree of 5-HT 2A receptor overexpression in the frontal cortex of depressed suicides, in agreement with data recently published (Pandey et al, 2002). In addition, positron emission tomography studies suggest that depressive and suicidal states are associated with increases of 5-HT 2 receptors and low levels of the 5-HT metabolite 5-hydroxyindoleacetic acid, which suggest reduced neurotransmitter concentrations (Meyer et al, 1999(Meyer et al, , 2003. Thus, as for a 2A -adrenoceptors, these increases in 5-HT 2A receptor density and function could be attributed to an increased rate of transcription.…”
Section: Altered 5-ht Receptor Expression In the Brains Of Suicide VIsupporting
confidence: 92%
“…In this work, we found a significant degree of 5-HT 2A receptor overexpression in the frontal cortex of depressed suicides, in agreement with data recently published (Pandey et al, 2002). In addition, positron emission tomography studies suggest that depressive and suicidal states are associated with increases of 5-HT 2 receptors and low levels of the 5-HT metabolite 5-hydroxyindoleacetic acid, which suggest reduced neurotransmitter concentrations (Meyer et al, 1999(Meyer et al, , 2003. Thus, as for a 2A -adrenoceptors, these increases in 5-HT 2A receptor density and function could be attributed to an increased rate of transcription.…”
Section: Altered 5-ht Receptor Expression In the Brains Of Suicide VIsupporting
confidence: 92%
“…Facial expressions of emotion elicit significantly greater activation in the left amygdala in subjects with BPD compared with normal controls (Donegan et al, 2003). Levels of pessimistic attitudes correlate directly with 5-HT2 receptor binding potential in depressed subjects, but not in those with BPD (Meyer et al, 2003). This does not rule out 5-HT dysfunction in BPD mediated by other 5-HT receptors.…”
Section: Pfcmentioning
confidence: 79%
“…A recent study by Bhagwagar et al (2006), in un-medicated, euthymic patients recovered from depression, support that a higher frontolimbic 5-HT 2A receptor level may be a trait factor of the susceptibility to develop depression and correlate positively with measures of negativistic thinking. Moreover, Meyer et al, 2003 found that in currently depressed patients, cortical, predominantly frontal, 5-HT 2 receptor binding was correlated to dysfunctional attitudes (pessimistic, negativistic thinking), whereas only the subgroup of patients with the most prominent negativistic thinking had a higher frontal 5-HT 2 receptor binding than healthy controls. As such, even in the depressed state, a positive association between negativistic thinking and frontal 5-HT 2A receptor binding seems to exist.…”
Section: Discussionmentioning
confidence: 95%
“…Additional evidence for 5-HT 2A receptor changes in depression comes from post-mortem studies in the subset of depressed patients that commit suicide of which the majority report that 5-HT 2A receptor binding is increased in dorsolateral prefrontal cortex (Stockmeier, 2003). Although initial findings of in vivo receptor imaging studies were contradictory, two recent studies have confirmed that frontal cortex 5-HT 2A receptor binding is increased, both in recovered, un-medicated patients with a history of major depression (Bhagwagar et al, 2006), and in un-medicated patients with severe depression (Meyer et al, 2003). Interestingly, negativistic thinking and 5-HT 2A receptor binding is correlated both in depressed patients (Bhagwagar et al, 2006;Meyer et al, 2003) and in healthy individuals (Frokjaer et al, 2008) in terms of dysfunctional attitudes and neuroticism scores, respectively.…”
Section: Introductionmentioning
confidence: 99%